مشرکین کے ساتھ مخاصمات میں مذکور اسماء الحسنیٰ کے اسرار و حِکم: Mysteries and wisdom of Asma al-Hasna mentioned in conversations with polytheists - Shamim Akhtar; Dr. Ammara Rehman (International Research Journal of Arabic and Islamic Studies, 2024)
Asma al-Hasna is mentioned in the Holy Qur'an at many places, it has a special relationship with the context, and in this context, Allah Almighty has mentioned His special names not only in the commandments and matters, but also in the chapter of faith. What has been said about the world religions in general and the distorted forms of Semitic religions in the beliefs and thoughts. Here it is also concluded that the original religion of the polytheists of Mecca was the "Deen-e-Hanif", that is why they called themselves "Hanifi" but they were addressed as "polytheists" because of malformation of their religion. With reference to the mystery and order of Asma al-Hasna, it is concluded that the mention of the names of Allah mentioned in the verses of Mukhasamat (مخاصمات) refers to a specific direction in each place, including "Divinity", "Lordship", "Oneness", "power", "perfection", "sovereignty", and "forgiveness" and many wisdoms of expressing others. In which there is advice, instruction and warning to the addressees.